2020
DOI: 10.31590/ejosat.677008
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of the pyrethroid insecticide deltamethrin degrading bacteria from insects

Abstract: Many studies have showed that the pesticide residues in the environment increase day by day because of their continuous use. Pesticides can degrade chemically, physically and biologically. Biodegradation is an eco-friendly, inexpensive and highly effective approach compared to other methods. Bacteria are the most commonly used biological agents in biodegradation studies. Widespread use of pyrethroid pesticides such as deltamethrin causes pollution of environment. A total of 14 bacterial isolates were isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…In addition, this study explained that eleven of them were gram-negative bacteria, and three were gram-positive bacteria, potentially deleting deltamethrin up to 100 mg/L. This study concluded that insecticide-tolerated gut microbiota is enriched with nutrients and is considered a powerful tool for the remediation of various kinds of pollutants from the ecosystem ( Özdal and Algur, 2020 ). An indigenous rod-shaped gram-negative bacterium was isolated from the digestive tract of a grasshopper ( Poecilimon tauricola ) for the potential biodegradation of α-endosulfan and α-cypermethrin.…”
Section: Functions Of Insect Gut Microbiotamentioning
confidence: 91%
“…In addition, this study explained that eleven of them were gram-negative bacteria, and three were gram-positive bacteria, potentially deleting deltamethrin up to 100 mg/L. This study concluded that insecticide-tolerated gut microbiota is enriched with nutrients and is considered a powerful tool for the remediation of various kinds of pollutants from the ecosystem ( Özdal and Algur, 2020 ). An indigenous rod-shaped gram-negative bacterium was isolated from the digestive tract of a grasshopper ( Poecilimon tauricola ) for the potential biodegradation of α-endosulfan and α-cypermethrin.…”
Section: Functions Of Insect Gut Microbiotamentioning
confidence: 91%
“…It is likely that the genera of bacteria for which an increase in abundance was recorded are tolerant to the insecticides used, or maybe they are able to degrade insecticides, making them less effective. The above‐mentioned genera of bacteria are known to degrade insecticides (Gilani et al, 2016 ; Ibrahim et al, 2021 ; Jaffar et al, 2022 ; Özdal & Algur, 2020 , 2022 ). For instance, Akami et al ( 2019 ) demonstrated that genera including Acinetobacter , Citrobacter , Pseudomonas , Burkholderiales (unclassified genera) are potentially involved in the increased tolerance of their insect host— Callosobruchus maculatus (Coleoptera, Chrysomelidae) against the dichlorvos insecticide (DDVP).…”
Section: Discussionmentioning
confidence: 99%
“…These bacteria were identi ed as P. aeruginosa B5, A. schindleri B7, B. megaterium B9, B. parabrevis B12 and A. johnsonii B6. These species have previously been used in the studies of degradation of different toxic compounds Ozdal and Algur 2020).…”
Section: Discussionmentioning
confidence: 99%